Sistem Informasi Penggajian Dan Perhitungan PPh 21 Pada PT. Lotron Indonesia Bekasi - Muspiawati, Reni; Arifin, Rita Wahyuni (BINA INSANI ICT JOURNAL; Vol 2 No 1 (2015): Bina Insani ICT Journal (Maret 2015), 2015)
Abstract: The era of globalization, information technology moving rapidly. The computer is the equipment created to facilitate human work, to achieve good progress in hardware and software.PT. Lotron Indonesia need an information system that support and facilitate the work process. To the writer tries to make research on the system of payroll and income tax reporting 21 PT. Lotron Indonesia which is still not computerized. PT. Lotron Indonesia is a company engaged in the textile field. Existing payroll system at PT. Lotron Indonesia is still done manually, from inputting attendance, payroll calculation, payroll and taxes, preparing reports salaries and taxes up to data storage - other data related to payroll processing up to journal entries, so as enable during the process occurs recording errors, lack of accurate statements are made and the delay in the search for the required data. Computerized system is the best solution to solve problems - problems that exist in this company, as well as the computerized system can achieve an activity which is effective and efficient in supporting the activities of this company. Keywords: Computerized system, Existing payroll system, Tax reporting 21 Abstrak: Era globalisasi sekarang ini, teknologi informasi melaju dengan pesat. Adapun komputer yang merupakan peralatan yang diciptakan untuk mempermudah pekerjaan manusia, sampai mencapai kemajuan baik di dalam hardware dan software.PT. Lotron Indonesia membutuhkan sebuah sistem informasi yang menunjang dan memberikan kemudahan dalam proses pekerjaannya. Untuk itu penulis mencoba membuat penelitian mengenai sistem penggajian karyawan dan pelaporan PPh 21 pada PT. Lotron Indonesia yang sampai saat ini masih belum terkomputerisasi.PT. Lotron Indonesia ini merupakan perusahaan yang bergerak